Color stability of glass ionomer cement in coloring solutions: integrative review (Research, Society and Development, 2022)
Background: Glass ionomer cement (GIC) has several indications in Dentistry, due to its biocompatibility properties, fluoride release and adhesion to dental tissues. Objective: To analyze the color stability of conventional GICs when immersed in coloring solutions based on data obtained in the literature. Methods: This is an integrative literature review carried out through searches in the databases PubMed, LILACS, SciELO and Cochrane Library, in which the following descriptors were used: “glass ionomer cement”, “cimentos de ionômeros de vidro”, “color”, “discoloration”, “pigmentação” e “cor”. Eligibility criteria included studies that evaluated the color stability of conventional GICs, full articles available for download, and texts published in English, Portuguese and Spanish. Clinical trials, laboratory studies and in situ studies were included and studies published in the last 25 years. Results: After analyzing the articles, 14 studies were included in the review. Predominantly, conventional GICs susceptibility to staining has been reported by immersion in coloring solutions, such as pigmenting substances from the diet, drugs in liquid form, fluoride gels, bleaching gels and biofilm-evidence solutions, in addition to laboratory dyes. On the other hand, some studies have found the color stability of conventional GICs compared to other restorative materials. Conclusions: Conventional GIC has variable color stability, depending on the dye solutions and experimental methods applied.